Constructing Hierarchical Porous Carbons With Interconnected Micro-mesopores for Enhanced CO2 Adsorption - Zhang, Hainan; Wang, Zeming; Luo, Xudong; Lu, Jinlin; Peng, Shengnan; Wang, Yongfei; Han, Lu (Frontiers in Chemistry, 2020)
A high cost-performance carbon dioxide sorbent based on hierarchical porous carbons (HPCs) was easily prepared by carbonization of raw sugar using commercially available nano-CaCO3 as a double-acting template. The effects of the initial composition and carbonization temperature on the micro-mesoporous structure and adsorption performance were examined. Also, the importance of post-activation behavior in the development of micropores and synthesis route for the formation of the interconnected micro-mesoporous structure were investigated. The results revealed excellent carbon dioxide uptake reaching up 2.84 mmol/g (25 oC, 1 bar), with micropore surface area of 786 m2/g, micropore volume of 0.320 cm3/g and mesopore volume of 0.233 cm3/g. We found that high carbon dioxide uptake was ascribed to the developed micropores and interconnected micro-mesoporous structure. As an expectation, the optimized HPCs offers a promising new support for the high selective capture of carbon dioxide in the future.